Visuospatial Cognitive Deficits and Subtle Cortical Anomalies in Preterm Adolescents - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
Voxel-based morphometric analysis (VBM) of the MRI scans of a group of adolescents, born preterm with very low birth weights and with deficits in judgment of line orientation, was used to demonstrate anomalies of cortical gray matter in a study at the Institute of Child Health and Great Ormond Street Hospital, London, UK.